ANALYSIS OF LANDSLIDE POTENTIAL ON SOIL EMBANKMENT SLOPES FOR HIGHWAY CONSTRUCTION - Maulana, Rizal
One form of highway construction to meet the requirements of horizontal and vertical alignments is embankment. Embankment contruction works must comply to compaction procedures to meet design criteria, which is shear strength of embankment body. This research was carried out on a soil embankment for a rayal road segment which is suspected to be unstable on one side of its slope. The investigation began by looking at reports when the embankment construction work was carried out, and continued by collecting soil parameter data, conducting geoelectric and hand drill tests, conducting Cone Penetration Test (CPT) tests. Based on the data, the modeling of embankment slope is then carried out for the purposes of slope stability analysis using the limit equilibrium method (LEM) and the finite element method (FEM)..